1982
DOI: 10.3758/bf03203313
|View full text |Cite
|
Sign up to set email alerts
|

An automated version of the digit symbol substitution test (DSST)

Abstract: An automated version of the Digit Symbol Substitution Test is described that employs a relatively inexpensive, commercially available microcomputer to present and score the task. Advantages of the automated DSST include: (1) objective scoring of both speed and accuracy of test performance, (2) printed copies of test scores, (3) convenient administration under standardized test conditions, and (4) the capacity for repeated assessment of an individual's performance over time. Task performance data for individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
218
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 359 publications
(219 citation statements)
references
References 14 publications
1
218
0
Order By: Relevance
“…Computerized psychomotor tasks (Haney et al 1999) consisted of a 3-min Digit-Symbol Substitution Task (DSST; McLeod et al 1982), a 3-min repeated-acquisition task (RA; Kelly et al 1993), a 10-min divided attention task (DAT; Miller et al 1988), a 10-min rapid information task (RIT; Wesnes and Warburton 1983), and a 3-min immediate and delayed digit-recall task (Hart et al 2001). …”
Section: Subjective-effects and Cognitive/psychomotor Batterymentioning
confidence: 99%
“…Computerized psychomotor tasks (Haney et al 1999) consisted of a 3-min Digit-Symbol Substitution Task (DSST; McLeod et al 1982), a 3-min repeated-acquisition task (RA; Kelly et al 1993), a 10-min divided attention task (DAT; Miller et al 1988), a 10-min rapid information task (RIT; Wesnes and Warburton 1983), and a 3-min immediate and delayed digit-recall task (Hart et al 2001). …”
Section: Subjective-effects and Cognitive/psychomotor Batterymentioning
confidence: 99%
“…A computerized version of the task (McLeod et al, 1982) has demonstrated dose-related impairment with psychoactive drugs such as ethanol (Mintzer et al, 1997;Roache et al, 1993). The task requires subjects to depress key positions on a numeric keypad to reproduce geometric symbol patterns displayed on the computer screen.…”
Section: Experimental Measuresmentioning
confidence: 99%
“…A computerized version of the DSST, which has been described previously, was used in this experiment (McLeod et al, 1982). Briefly, participants used a numeric keypad to enter a geometric pattern associated with one of nine digits displayed on a video screen.…”
Section: Digit-symbol-substitution Test (Dsst)-mentioning
confidence: 99%